Enhancing nutrients use efficiency and grain yield of Zea mays L. cultivated on a tropical acid soil using paddy husk compost and clinoptilolite zeolite - Omar, Latifah; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (National Center for Agrarian Sciences of Bulgaria, 2017)
With the ever increasing food demand coupled with environmental pollution due to unbalanced use of chemical fertilizers, there is a need to mitigate nutrients use effi ciency to improve crop productivity. A fi eld study was carried out from April 2014 to August 2014 on Nyalau Series (Typic Tualemkuts) to determine the effects of chemical fertilizers, compost, and clinoptilolite zeolite on: (i) selected soil chemical availability, nutrients uptake and use effi ciency and (ii) grain yield of Zea mays L. The fi eld study was conducted for 72 days for two consecutive planting cycles of Zea mays L. The use of chemical fertilizers, compost, and clinoptilolite zeolite improved nutrients use effi ciency and grain yield of Zea mays L. because of nutrients released from compost and retention of exchangeable cations on the exchange sites of clinoptilolite zeolite. The use of chemical fertilizers, compost, and clinoptilolite zeolite does not only improved timely uptake of nitrogen, phosphorus, potassium, calcium, magnesium, and sodium in the aboveground biomass of Zea mays L. but also affects the higher grain yield of Zea mays L. compared with chemical fertilizers only. Application of chemical fertilizers, compost, and clinoptilolite zeolite can improve nutrients availability, uptake and use effi ciency, so was grain yield of Zea mays L.